Cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation and preparation method thereof
By adding cobalt and aluminum to the nickel-based high-temperature alloy, a heterostructure is formed and a nanocrystalline oxide lubricating layer is formed through discharge plasma sintering process, the low strength, low toughness and high-temperature corrosion and wear of existing high-temperature self-lubricating composite materials in high-temperature environments is solved, and excellent self-lubricating performance at high temperatures is achieved.
Patent Information
- Application Number
- CN202411898715.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
AI Technical Summary
Existing high-temperature self-lubricating composites have problems such as low strength, low toughness and high-temperature corrosion and wear-induced failure in high-temperature environments.
By adding an appropriate amount of cobalt and aluminum to the nickel-based high-temperature alloy, a heterostructure with a multi-stage grain size is formed, and a surface-intensive nanocrystalline oxide lubricating layer is formed through discharge plasma sintering process to regulate the friction oxidation process to achieve high-temperature self-lubricating.
It achieves high-temperature self-lubricating properties with high compression strength, compressive strength, low friction coefficient and low wear rate at high temperatures of 600℃ and 800℃, extending the service life of the material.
Smart Images

Figure CN119736520A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of high-temperature corrosion and self-lubrication, and specifically relates to a cobalt-aluminum-modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation and a preparation method thereof. Background Art
[0002] High temperature friction and wear have always been the key issues faced by core mechanical components such as aviation bearings, turbine blades, and locomotive key components in extreme working environments, seriously affecting the durability and safety of the technology. In order to improve efficiency and extend the service life of equipment, people have conducted a lot of research to design and produce new materials with reliable wear resistance and friction reduction capabilities as well as good mechanical properties, and can continue to maintain these optimized characteristics.
[0003] However, problems coexist with attempts. The self-lubricating coating sprayed on the surface of the equipment has disadvantages such as weak adhesion, mismatched thermal expansion coefficients, and mutual diffusion between the coating and the substrate, which can easily cause functional degradation and low durability. Liquid lubricants (oils and greases) are the most commonly used lubricants, but they decompose and degrade rapidly when exposed to high temperatures. Experience has shown that adding traditional solid lubricants such as graphite, hexagonal boron nitride, transition metal disulfides, fluorides and soft metals to alloys is either effective in a limited temperature range below 600°C, or significantly reduces strength and toughness. Based on the above situation, people realize that it is very important to produce an alloy that has both high-temperature self-lubricity and oxidation resistance, that is, to solve the mechanical / mechanical trade-off problem.
[0004] At high temperatures, the metal substrate is susceptible to oxidation. Previous studies have found that certain metal oxides have lubricity. In this regard, controlling the oxidation of the substrate and generating the desired oxide, rather than adding lubricants, may be an effective way to achieve high-temperature self-lubrication while avoiding a significant reduction in toughness. It is well known that during the friction process, a dense oxide layer is usually formed on the contact surface of the alloy, which effectively reduces the friction coefficient and wear rate. Many studies have confirmed that cobalt has advantages in forming this tri-oxide layer and reducing wear. Frederick et al. found that adding more than 11 at.% Co can reduce the oxidation activation energy to 200 kJ mol -1 Ariane Viat et al. compared the friction and wear behaviors between Co / / Co, Cr / / Cr and Ni / Ni at 100 ~ 600℃ and found that only Co / / Co contact can form a trioxide protective layer, the main components of which are Co3O4 and mixed spinel (Ni, Cr) x Co 3-xO4. The research of Alixe Dreano et al. shows that when the temperature is higher than 400℃, the Cr-Ni-W solid solution (HS25) reacts with alumina to form a third protective body spontaneously at the interface, and the effective wear-resistant glaze layer is composed of nanocrystalline cobalt oxide. In short, the use of cobalt oxide for lubrication is a reasonable and feasible option.
[0005] Even so, maintaining the mechanical properties of the alloy simply by avoiding the use of lubricants is still unsatisfactory. People expect to obtain better strength and toughness while ensuring that the alloy has excellent high-temperature tribological properties. Recently, a lot of research work has focused on microstructure control. Heterogeneous structures are believed to be able to overcome the trade-off between strength and toughness of traditional homogeneous structural materials, which arises from back stress strengthening, also known as heterogeneous deformation induced strengthening (HDI). To date, people have been working hard to develop metal materials with structural heterogeneity. In an ODS Fe-10Cr-6.1Al-0.3Zr-0.1Y alloy, a bimodal grain size distribution was achieved by internal oxidation and sintering of oxide particle-decorated powder particles, thereby obtaining ideal mechanical properties, with YS of 598 MPa, UTS of 734 MPa, and elongation at break of 25.1%. Feng He et al. developed Ni2CoCrFeTi with grain-scale heterogeneous structure by single-step rolling and annealing. 0.24 Al 0.2 HEA, the material shows an excellent strength-conductivity combination, with a yield strength of about 1.3GPa and a tensile elongation of about 20%. Layered structure powder metallurgy stainless steel, heterogeneous thin film (HL) Fe 35 Ni 35 Cr 25 Similar outstanding results have been achieved in the research of Mo5 alloy and heterostructure Co-Cr-Ni medium entropy alloy. Combining the back stress strengthening of heterostructures with traditional strengthening strategies, including fine grain strengthening, solid solution strengthening, precipitation strengthening, MBIP, TWIP and TRIP, can make the alloy have higher strength, better ductility, higher work hardening rate and stronger fracture toughness. However, the research on the effect of heterostructure on high temperature wear is obviously insufficient. According to the research of Xu et al., in Fe 35 Ni 35 Cr 25 Adjusting the content of Co and Cr in Mo5 to regulate grain refinement and precipitation of hard phase σ chromium can significantly improve room temperature mechanical strengthening and the formation of lubricating layer at 400 ℃. 30 Cr 28 Ni 27Grain grading and composition fluctuation are achieved in Al7Cu6 / Ti6B2 HEA, resulting in excellent mechanical and anti-wear properties over a wide temperature range up to 800°C. Therefore, we have reason to believe that the synergistic optimization of mechanical-tribological-corrosion properties can be achieved by combining composition control with microstructure design. Summary of the invention
[0006] The purpose of the present invention is to provide a cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation and a preparation method thereof. Based on the differences in thermodynamics and kinetics of high-temperature oxidation of alloy elements, the alloy composition is regulated to induce the formation of a multilayer structural friction product with self-lubricating and anti-oxidation effects during high-temperature friction, thereby solving the problems of low strength, low toughness and high-temperature corrosion and wear-induced failure of self-lubricating composite materials in the prior art, and can be applied to the production of motion and transmission parts in high-temperature atmospheric environments and under high loads.
[0007] The technical solution of the present invention is: A cobalt-aluminum-modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation. The composite material is prepared by spark plasma sintering with micron-sized nickel-based high-temperature alloy powder as the base powder, mixed with cobalt powder and aluminum powder, and has a heterogeneous structure with multi-level grain sizes and a smooth and dense nanocrystalline oxide lubricating layer on the surface; the mass percentages of the original powders are: 55-70% nickel-based alloy powder, 20-40% cobalt powder, and 3-8% aluminum powder, and the particle sizes of the original powders are 30-50 μm for nickel-based alloy powder, 2 μm for cobalt powder, and 2 μm for aluminum powder.
[0008] Furthermore, in the cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation, preferably, the nickel-based alloy powder is micron-sized NiCr, FGH97 or In738 alloy powder.
[0009] Furthermore, in the cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation, the cobalt powder can be replaced by cobalt-chromium alloy or cobalt-chromium-tungsten alloy powder, and the aluminum powder can be replaced by nickel-aluminum alloy, cobalt-aluminum alloy or nickel-cobalt-aluminum alloy powder.
[0010] Furthermore, the cobalt-aluminum-modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation has the following performance indicators: compression strength ≥ 1300 MPa or no crushing, compression deformation rate ≥ 30%; at 600°C, reciprocating friction coefficient ≤ 0.35, wear rate ≤ 5×10 -5 mm 3 / Nm, at 800℃, reciprocating friction coefficient ≤ 0.35, wear rate ≤ 5×10 -6 mm 3 / Nm.
[0011] The above-mentioned method for preparing a cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation comprises the following preparation steps: (1) Powder mixing: Use a ball mill to mix the original powder weighed according to the formula, with a rotation speed of 200 to 400 r / min, running for 30 minutes and stopping for 15 minutes, and the ball milling time is 10 to 20 hours, and the obtained powder is dried; (2) Cold pressing by mold loading: first, evenly spray boron nitride on the graphite mold for sintering, then fill the inner wall of the graphite mold with graphite paper, then load the powder obtained in step (1) into the graphite mold, and use a hydraulic press to pre-press and hold the loaded powder; use a universal testing machine to pressurize and hold it, and then unload it; (3) Spark plasma sintering: Place the graphite mold filled with powder into the sintering furnace and perform pressure sintering according to the process of "heating-keeping-cooling". Keep the gas pressure in the graphite mold below 1×10 -3 atm, and the sintering pressure is 35 ~50 MPa.
[0012] Furthermore, in the preparation method of the cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation, in step (1), the ball milling process uses a stainless ball milling jar and stainless steel balls, and the ball-to-material mass ratio is 10:1. The ball milling jar loaded with the original powder will be placed in a planetary ball mill, and n-heptane accounting for 0.3 to 1% of the mass fraction of the original powder is added as a ball milling aid.
[0013] Furthermore, in the method for preparing the high-temperature resistant, high-strength and high-toughness metal-based self-lubricating composite material based on oxidation regulation, in step (2), the hydraulic press pre-presses the loaded powder at 20 to 30 MPa and holds the load for 60 seconds; the universal testing machine is used to pressurize the powder to 70 to 80 kN and maintain the pressure for 2 minutes.
[0014] Furthermore, in the method for preparing the high-temperature resistant, high-strength and high-toughness metal-based self-lubricating composite material based on oxidation regulation, in step (3), the "heating" is divided into two stages, firstly heating to 1050°C at a rate of 45 to 55°C / min, and then heating to 1100°C at a rate of 15 to 25°C / min; when the final sintering temperature is 1100°C, it is kept warm for 10 to 20 minutes and then cooled to room temperature in the furnace.
[0015] The design concept of the present invention is: After adding an appropriate amount of cobalt to alloys such as NiCr, FGH97 or In738, after mechanical alloying and spark plasma sintering, a heterogeneous structure with multi-level grain sizes can be formed, and the second phase can be refined and evenly distributed, and the strength of the alloy can be improved through fine grain strengthening, back stress strengthening and precipitation strengthening. The addition of cobalt can also cause the alloy to produce cobalt-rich oxides with low ionic potential, low shear modulus and low melting point during high-temperature friction and wear, and sinter under the action of friction heat and reciprocating compaction to form a smooth and dense nanocrystalline oxide lubrication layer. The heterogeneous structure provides a large number of grain boundary fast channels for the diffusion of cobalt inside the alloy to the surface, so that cobalt can be replenished in time to generate enough oxides to form a complete lubrication layer. The formation of a dense lubrication layer can reduce the oxygen partial pressure at the interface with the alloy, promote the selective oxidation of Al, and thus generate a continuous aluminum oxide layer, which plays a role in hindering the inward diffusion of oxygen and the outward diffusion of alloy elements. It can not only improve the oxidation resistance of the alloy and alleviate oxidation wear, but also inhibit the excessive thickening of the lubrication layer and avoid the cracking of the lubrication layer due to excessive internal stress. At the same time, the alumina layer can also enhance the bonding force between the lubricating layer and the alloy, preventing the lubricating layer from peeling off under shear force. The good strength and toughness of the heterogeneous structure and the double-layer lubricating layer composed of a cobalt-rich oxide lubricating layer and an alumina layer work together to reduce friction and wear, avoiding severe wear in the early stages of alloy wear and the problem that traditional self-lubricating composite materials cannot serve for a long time. In addition, the composite material does not contain brittle ceramic phases and low-strength and toughness lubricating phases such as soft metals and graphite, retaining the high strength and high toughness characteristics of the metal matrix. In summary, the composite material has excellent comprehensive properties such as anti-oxidation, high strength, high toughness, low friction coefficient and low wear rate.
[0016] The advantages and beneficial effects of the present invention are: (1) The composite material prepared by the present invention has a simple preparation process, low cost, and the raw materials in the formula are easily available; (2) The composite material prepared by the present invention has high flexural strength and compressive strength and excellent mechanical properties; (3) The composite material prepared by the present invention has excellent tribological properties at high temperatures of 600°C and 800°C, and can provide good wear-resistant lubrication effect for a long time; (4) The composite material prepared by the present invention has good high-temperature performance and processability, good electrical and thermal conductivity, and can be easily processed into hot end components of various shapes and sizes. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 :(a) The microstructure of a high-temperature self-lubricating composite material with good density and mechanical properties prepared by spark plasma sintering process; (b) The wear scar morphology of the composite material after reciprocating friction and wear test at 600℃; (c) The wear scar morphology of the composite material after reciprocating friction and wear test at 800℃; Figure 2 : (a) is the microstructure of the self-lubricating composite material without cobalt addition; (b) is the wear scar morphology of the composite material without cobalt addition after reciprocating friction and wear test at 600°C; (c) is the wear scar morphology of the composite material without cobalt addition after reciprocating friction and wear test at 800°C. DETAILED DESCRIPTION
[0018] The following examples are further detailed descriptions of the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Example 1
[0019] In this embodiment, micron-sized NiCr alloy powder (NiCr powder composition: Ni80wt%, Cr20wt%) is used as a matrix, and is mixed with cobalt powder and aluminum powder to prepare the composite material, wherein: the particle size of the Ni20Cr alloy powder is about 30 ~ 50 μm, the particle size of the cobalt powder is about 2 μm, and the particle size of the aluminum powder is about 2 μm. Boron nitride is first evenly sprayed on the graphite mold for sintering, and then graphite paper is filled on the inner wall of the graphite mold. The specific preparation parameters of the composite material are as follows: (1) Powder mixing: The composite material has the following composition ratio: Ni20Cr alloy powder 67 wt%, cobalt powder 30 wt%, aluminum powder 3 wt%. The ball milling process uses a stainless ball milling jar and stainless steel balls with a ball-to-material mass ratio of 10:1. The ball milling jar filled with the original powder will be placed in a planetary ball mill, and n-heptane with a mass fraction of 0.5% of the original powder will be added as a process control agent to prevent the powder from cold welding and sticking to the jar during the ball milling process. The powders are mixed evenly in a planetary ball mill with a rotation speed of 300 r / min. The mill runs for 30 min and stops for 15 min. After ball milling for 20 h, the homogenized powder is dried.
[0020] (2) Spark plasma sintering: The final mixed and dried powder is placed in a graphite mold and compacted by a hydraulic press. The hydraulic press pre-presses the graphite mold filled with powder at 24 MPa and holds the load for 60 seconds. The universal testing machine is used to pressurize the graphite mold to 76 kN and maintain the pressure for 2 minutes. The spark plasma sintering equipment is used to pressurize the graphite mold according to the process of "heating-maintaining-cooling": the air pressure in the graphite mold is maintained at 5×10 -4 atm, and the sintering pressure is 40 MPa. The "heating" stage is divided into two steps. The first step is to raise the temperature to 1050℃ at a heating rate of 50℃ / min; the second step is to raise the temperature to 1100℃ at a heating rate of 20℃ / min, and finally keep the temperature at 1100℃ for 15 minutes and then cool to room temperature.
[0021] The density of the sintered composite material is 98.6% and the hardness is 356 Hv 0.2The compressive yield strength is 812 MPa, the compressive strength is 2532 MPa, the compression deformation rate is 32.94%, and it is not crushed. The friction and wear test load is 10 N, the grinding pair is a silicon nitride ceramic ball with a diameter of 9.525 mm, the reciprocating friction time is 30 min, the linear speed is 0.024 m / s, the average friction coefficient at 600℃ is 0.32, and the wear rate is 7.9×10 -6 mm 3 / Nm. The average friction coefficient at 800℃ is 0.30, and the wear rate is 2.3×10 -6 mm 3 / Nm. Figure 1 As shown in (a), the composite material of Ni20Cr-30Co-3Al has a dense structure, no obvious holes and defects, small primary particle size, many boundaries, and fine and uniformly distributed second phase. Figure 1 As shown in (b), the wear scar is basically covered with a friction oxide layer, with no serious peeling and deep furrows, only some cracks and shallow furrows. Figure 1 As shown in (c), the wear scar is covered with a dense and continuous friction oxide layer, without obvious defects such as peeling, furrows and cracks, which effectively prevents direct contact wear between the wear pair and the composite surface, while reducing the actual contact area between the friction pairs, and obtaining excellent tribological properties. Figure 2 As shown in (a), the original particle size of the Ni20Cr-3Al composite material without cobalt addition is larger, the boundary is less, and the second phase particle size is larger. Figure 2 As shown in (b), severe abrasive wear and adhesive wear occurred in the wear scar, and no continuous enamel layer was formed on the surface. Figure 2 As shown in (c), there is a large area of spalling and clear furrows in the wear scar, and the exposed matrix has undergone severe plastic deformation. Comparative Example 1
[0022] The difference from Example 1 is that the composition ratio of the composite material is 97 wt % of Ni20Cr powder, 0 wt % of cobalt powder, and 3 wt % of aluminum powder.
[0023] The density of the sintered composite material is 97.7% and the hardness is 301 Hv 0.2 The compression yield strength is 484 MPa, the compressive strength is 2052 MPa, the compression deformation rate is 32.16%, and the crushing is achieved. The average friction coefficient at 600℃ is 0.38, and the wear rate reaches 8.98×10 -4 mm 3 / Nm. The average friction coefficient at 800℃ is 0.40, and the wear rate reaches 1.61×10 -5 mm3 / Nm. Comparative Example 2
[0024] The difference from Example 1 is that the composition ratio of the composite material is 87 wt % of Ni20Cr alloy powder, 10 wt % of cobalt powder, and 3 wt % of aluminum powder.
[0025] The density of the sintered composite material is 98.3% and the hardness is 333 Hv 0.2 The compression yield strength is 637 MPa, the compressive strength is 2296 MPa, and the crushing is achieved. The average friction coefficient at 600℃ is 0.35, and the wear rate is 5.26×10 -5 mm 3 / Nm. The average friction coefficient at 800℃ is 0.35, and the wear rate is 8.1×10 -6 mm 3 / Nm. Comparative Example 3
[0026] The difference from Example 1 is that the composition ratio of the composite material is 47 wt % of Ni20Cr alloy powder, 50 wt % of cobalt powder, and 3 wt % of aluminum powder.
[0027] After sintering, the density of the composite material is 98.5% and the hardness is 378 Hv 0.2 The compression yield strength is 886 MPa, the compressive strength is 2473 MPa, and the crushing is achieved. The average friction coefficient at 600℃ is 0.34, and the wear rate is 3.97×10 -4 mm 3 / Nm. The average friction coefficient at 800℃ is 0.33, and the wear rate is 6.52×10 -5 mm 3 / Nm. Example 2
[0028] In this embodiment, micron-sized FGH97 alloy powder (the composition of FGH97 alloy powder is: C 0.04 wt%, Co 15.9wt%, Cr 8.9 wt%, W 5.6 wt%, Mo 3.8 wt%, Al 5.0 wt%, Ti 1.8 wt%, Nb 2.6 wt%, Hf 0.3wt%, and the balance is Ni) is used as a matrix, and the particle size is in the range of 30 to 50 μm. It is mixed with cobalt powder and aluminum powder to prepare the composite material. The particle size of the cobalt powder is about 2 μm, and the particle size of the aluminum powder is about 2 μm. Boron nitride is first evenly sprayed in a graphite mold for sintering, and then graphite paper is filled on the inner wall of the graphite mold. The specific preparation parameters of the composite material are as follows: (1) Powder mixing: The composite material has the following composition ratio: 67 wt% FGH97 alloy powder, 30 wt% cobalt powder, and 3 wt% aluminum powder. The ball milling process uses a stainless ball mill and stainless steel balls with a ball-to-material mass ratio of 10:1. The ball mill filled with the original powder will be placed in a planetary ball mill, and n-heptane with a mass fraction of 0.5% of the original powder will be added as a process control agent to prevent the powder from cold welding and sticking to the mill during the ball milling process. The powders are mixed evenly in a planetary ball mill with a rotation speed of 300 r / min. The mill runs for 30 min and stops for 15 min. After ball milling for 20 h, the homogenized powder is dried.
[0029] (2) Spark plasma sintering: The final mixed and dried powder is placed in a graphite mold and compacted by a hydraulic press. The hydraulic press pre-presses the graphite mold filled with powder at 21 MPa and holds the load for 60 seconds; the universal testing machine is used to pressurize to 78 kN and maintain it for 2 minutes. The spark plasma sintering equipment is used to pressurize and sinter according to the process of "heating-keeping-cooling": the air pressure in the graphite mold is maintained at 3×10 -4 atm, and the sintering pressure is 40 MPa. The "heating" stage is divided into two steps. The first step is to raise the temperature to 1050℃ at a heating rate of 50℃ / min; the second step is to raise the temperature to 1100℃ at a heating rate of 20℃ / min, and finally keep the temperature at 1100℃ for 15 minutes and then cool to room temperature.
[0030] After sintering, the density of the composite material is 98.6% and the hardness is 420 Hv 0.2 , the compressive yield strength is 1026 MPa, the compressive strength is 2165 MPa, and the compression deformation rate is 22.5%. The friction and wear test load is 10 N, the grinding pair is a silicon nitride ceramic ball with a diameter of 9.525 mm, the reciprocating friction time is 30 min, the linear speed is 0.024 m / s, the average friction coefficient at 600 ° C is 0.35, and the wear rate is 1.8×10 -5 mm 3 / Nm. The average friction coefficient at 800℃ is 0.34, and the wear rate is 4×10 -6 mm 3 / Nm. , Example 3
[0031] In this embodiment, micron-sized In738 alloy powder is used as a matrix (the composition of In738 alloy powder is: C 0.17 wt%, Co 8.12 wt%, Cr 15.92 wt%, W 2.61 wt%, Mo 1.8 wt%, Al 3.6 wt%, Ti 3.49 wt%, Nb 0.94wt%, Ta 1.78 wt%, and the balance is Ni) as a matrix, and the particle size is in the range of 30 to 50 μm, and is mixed with cobalt powder and aluminum powder to prepare the composite material. The particle size of the cobalt powder is about 2 μm, and the particle size of the aluminum powder is about 2 μm. Boron nitride is first evenly sprayed in a graphite mold for sintering, and then graphite paper is filled on the inner wall of the graphite mold. The specific preparation parameters of the composite material are as follows: (1) Powder mixing: The composite material has the following composition ratio: 67 wt% In738 alloy powder, 30 wt% cobalt powder, and 3 wt% aluminum powder. The ball milling process uses a stainless ball milling jar and stainless steel balls with a ball-to-material mass ratio of 10:1. The ball milling jar filled with the original powder will be placed in a planetary ball mill, and n-heptane with a mass fraction of 1% of the original powder will be added as a process control agent to prevent the powder from cold welding and sticking to the jar during the ball milling process. The powders are mixed evenly in a planetary ball mill with a rotation speed of 300 r / min. The mill runs for 30 min and stops for 15 min. After ball milling for 20 h, the homogenized powder is dried.
[0032] (2) Spark plasma sintering: The final mixed and dried powder is placed in a graphite mold and compacted by a hydraulic press. The hydraulic press pre-presses the graphite mold filled with powder at 23 MPa and holds the load for 60 seconds; the universal testing machine is used to pressurize to 71 kN and maintain it for 2 minutes. The spark plasma sintering equipment is used to pressurize and sinter according to the "heating-maintaining-cooling" process: the air pressure in the graphite mold is maintained at 6×10 -4 atm, and the sintering pressure is 40 MPa. The "heating" stage is divided into two steps. The first step is to raise the temperature to 1050℃ at a heating rate of 50℃ / min; the second step is to raise the temperature to 1100℃ at a heating rate of 20℃ / min, and finally keep the temperature at 1100℃ for 15 minutes and then cool to room temperature.
[0033] After sintering, the density of the composite material is 98.5% and the hardness is 405 Hv 0.2 , the compressive yield strength is 700 MPa, the compressive strength is 1307 MPa, and the compression deformation rate is 24.8%. The friction and wear test load is 10 N, the grinding pair is a silicon nitride ceramic ball with a diameter of 9.525 mm, the reciprocating friction time is 30 min, the linear speed is 0.024 m / s, the average friction coefficient at 600 ° C is 0.35, and the wear rate is 1.2×10 -5 mm 3 / Nm. The average friction coefficient at 800℃ is 0.34, and the wear rate is 3.9×10 -6 mm 3 / Nm. Example 4
[0034] The difference from Example 3 is that the composite material is prepared by using cobalt-chromium alloy powder with an equivalent particle size of 2 μm instead of cobalt powder, and its component ratio is 67 wt % of In738 alloy powder, 30 wt % of cobalt-chromium alloy powder, and 3 wt % of aluminum powder.
[0035] After sintering, the average friction coefficient of the composite material at 600℃ is 0.35 and the average wear rate is 2×10 -5 mm 3 / Nm. The average friction coefficient at 800℃ is 0.34, and the wear rate is 3.3×10 -6 mm 3 / Nm. Example 5
[0036] The difference from Example 3 is that the composite material is prepared by using cobalt-chromium-tungsten alloy powder with an equivalent particle size of 2 μm instead of cobalt powder, and its component ratio is 67 wt% of In738 alloy powder, 30 wt% of cobalt-chromium-tungsten powder, and 3 wt% of aluminum powder.
[0037] After sintering, the average friction coefficient of the composite material at 600℃ is 0.35, and the wear rate is 1.1×10 -5 mm 3 / Nm. The average friction coefficient at 800℃ is 0.34, and the wear rate is 4.2×10 -6 mm 3 / Nm. Example 6
[0038] The difference from Example 3 is that the composite material is prepared by using cobalt-chromium alloy powder with an equivalent particle size of 2 μm instead of cobalt powder, and nickel-aluminum alloy powder instead of aluminum powder, and its composition ratio is 67 wt% In738 alloy powder, 30 wt% cobalt-chromium alloy, and 3 wt% nickel-aluminum alloy powder.
[0039] After sintering, the average friction coefficient of the composite material at 600℃ was 0.35, and the wear rate reached 1.6×10 -5 mm 3 / Nm. The average friction coefficient at 800℃ is 0.34, and the wear rate is 3.9×10 -6 mm 3 / Nm. Example 7
[0040] The difference from Example 3 is that the composite material is prepared by replacing cobalt powder with cobalt-chromium alloy with an equivalent particle size of 2 μm, and replacing aluminum powder with cobalt-aluminum alloy powder, and its composition ratio is 67 wt% of In738 alloy powder, 30 wt% of cobalt-chromium alloy, and 3 wt% of cobalt-aluminum alloy powder.
[0041] After sintering, the average friction coefficient of the composite material at 600℃ was 0.35, and the wear rate reached 1.5×10 -5 mm 3 / Nm. The average friction coefficient at 800℃ is 0.34, and the wear rate is 3.8×10 -6 mm 3 / Nm. Example 8
[0042] The difference from Example 3 is that the composite material is prepared by replacing cobalt powder with cobalt-chromium alloy powder with an equivalent particle size of 2 μm, and replacing aluminum powder with nickel-cobalt-aluminum alloy powder, and its composition ratio is 67 wt% of In738 alloy powder, 30 wt% of cobalt-chromium alloy powder, and 3 wt% of nickel-cobalt-aluminum alloy powder.
[0043] After sintering, the average friction coefficient of the composite material at 600℃ was 0.35, and the wear rate reached 1×10 -5 mm 3 / Nm. The average friction coefficient at 800℃ is 0.34, and the wear rate is 4.3.×10 -6 mm 3 / Nm.
[0044] The implementation results show that the composite material of the embodiment of the present invention adopts micron-grade NiCr, FGH97 or In738 alloy powder as the base powder, and the mass percentages of the original powders are: 55-70% nickel-based alloy powder, 20-40% cobalt powder, and 3-8% aluminum powder. A specific preparation method is further adopted, especially during spark plasma sintering, and the "heating" is divided into two stages. First, it is heated to 1050°C at a rate of 45-55°C / min, and then heated to 1100°C at a rate of 15-25°C / min; when the final sintering temperature is 1100°C, it is kept warm for 10-20 minutes and then cooled to room temperature in the furnace. Thus, a high-temperature resistant, high-strength and high-toughness metal-based self-lubricating composite material based on oxidation regulation is obtained, and its optimized performance indicators are: the compressive yield strength reaches more than 800 MPa, the compressive strength reaches more than 2300 MPa, and the compression deformation rate of crushing reaches more than 30%; at 600°C, the reciprocating friction coefficient is ≤ 0.35, and the wear rate is ≤ 5×10 -5 mm 3 / Nm. At 800℃, the reciprocating friction coefficient is ≤ 0.35, and the wear rate is ≤ 5×10 -6 mm 3 / Nm.
[0045] The applicant declares that although the detailed composition and preparation method of the present invention have been shown and described, it is clear to those skilled in the art that the present invention is not limited to the above detailed composition and preparation method. Any improvement of the present invention, substitution of product raw materials and addition of auxiliary components, etc., are within the scope of protection and disclosure of the present invention.
Claims
1. A cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation, characterized in that: The composite material is made of micron-grade nickel-based alloy powder as the base powder, mixed with cobalt powder and aluminum powder, and prepared by spark plasma sintering. It has a heterogeneous structure with multi-level grain sizes and a smooth and dense nanocrystalline oxide lubrication layer on the surface; the mass percentages of the original powders are: 55 ~ 70% nickel-based alloy powder, 20 ~ 40% cobalt powder, and 3 ~ 8% aluminum powder. The particle sizes of the original powders are 30 ~ 50 μm for nickel-based alloy powder, 2 μm for cobalt powder, and 2 μm for aluminum powder.
2. A cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation according to claim 1, characterized in that: The nickel-based alloy powder is micron-sized NiCr, FGH97 or In738 alloy powder.
3. A cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation according to claim 1, characterized in that: Cobalt powder can be replaced by cobalt-chromium alloy or cobalt-chromium-tungsten alloy powder, and aluminum powder can be replaced by nickel-aluminum alloy, cobalt-aluminum alloy or nickel-cobalt-aluminum alloy powder.
4. A cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation according to claim 1, characterized in that: The performance indicators of the composite material are: compression strength ≥ 1300 MPa or no crushing, compression deformation rate ≥ 30%; at 600℃, reciprocating friction coefficient ≤ 0.35, wear rate ≤ 5×10 -5 mm 3 / Nm, at 800℃, reciprocating friction coefficient ≤ 0.35, wear rate ≤ 5×10 -6 mm 3 / Nm.
5. A method for preparing a cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation according to any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: (1) Powder mixing: Use a ball mill to mix the original powder weighed according to the formula, with a rotation speed of 200 to 400 r / min, running for 30 minutes and stopping for 15 minutes, and the ball milling time is 10 to 20 hours, and the obtained powder is dried; (2) Cold pressing: first, evenly spray boron nitride on the graphite mold for sintering, then fill the inner wall of the graphite mold with graphite paper, then fill the powder obtained in step (1) into the graphite mold, and use a hydraulic press to pre-press and maintain the filled powder; Use the universal testing machine to pressurize and maintain the pressure, then unload; (3) Spark plasma sintering: Place the graphite mold filled with powder into the sintering furnace and perform pressure sintering according to the process of "heating-keeping-cooling". Keep the gas pressure in the graphite mold below 1×10 -3 atm, and the sintering pressure is 35 ~ 50 MPa.
6. The method for preparing a cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation according to claim 5, characterized in that: In step (1), the ball milling process uses a stainless ball milling jar and stainless steel balls, with a ball-to-material mass ratio of 10:
1. The ball milling jar loaded with the original powder will be placed in a planetary ball mill, and n-heptane accounting for 0.3 to 1% of the mass fraction of the original powder will be added as a ball milling aid.
7. The method for preparing a cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation according to claim 5, characterized in that: In step (2), the hydraulic press pre-presses the powder at 20 to 30 MPa and holds the load for 60 seconds; the universal testing machine presses the powder to 70 to 80 kN and holds the pressure for 2 minutes.
8. The method for preparing a cobalt-aluminum modified nickel-based high-temperature self-lubricating composite material based on friction oxidation regulation according to claim 5, characterized in that: In step (3), "heating" is divided into two stages. First, heating to 1050°C at a rate of 45 to 55°C / min, and then heating to 1100°C at a rate of 15 to 25°C / min. When the final sintering temperature is 1100°C, the temperature is kept at 10 to 20 minutes and then the furnace is cooled to room temperature.